Analysis of Health Tourism Potential in The Minanga Community Health Center Working Area, Manado City - Welong S. Surya; Marieska Y. Waworuntu; Augustinus R. Butarbutar (International Journal of Health and Social Behavior, 2024)
Health tourism is a tourist travel activity to a tourist destination with the aim of receiving treatment or improving health and fitness. This research is a descriptive qualitative analysis by looking at case studies about the potential of health tourism. The research informants are doctors, dentists, nurses and pharmacists, and 5 pharmacists. The data was analyzed using the content analysis method on interview documents. The results of the research show that the importance of understanding and knowledge of health workers is to be able to improve the quality of service when facing tourist visits. When they have a health problem or want to improve their health condition while traveling, the attitude of health workers needs to be improved in terms of their competence which must be developed, services must comply with standards. operational procedures and being friendly and polite to tourists during health services. The conclusion of this research is that the understanding of each health worker is good regarding health tourism.